Improvements of turbulence model for analysis of hydrogen stratification erosion by turbulent buoyant jet. (January 2021) - Tong, Lili; Guo, Dingqing; Wang, Di; Cao, Xuewu
Highlights: Current turbulence model and parameter effects on erosion rate is evaluated. A modified k-ε model based on generalized gradient diffusion hypothesis is developed. Evaluation of model improvement effect is conducted. Abstract: Light gas stratification erosion by steam turbulent buoyant jet is the typical phenomenon about containment thermal hydraulics and hydrogen safety. Overprediction of stratification erosion rate has been observed in computational fluid dynamics (CFD) analysis by using current turbulence model based on simple gradient diffusion hypothesis (SGDH). To solve this problem, the effects of buoyancy term, coefficient and turbulent Schmidt number are discussed and a modified k-ε model with buoyancy term based on generalized gradient diffusion hypothesis (GGDH) which contains vertical and horizontal density gradient is developed. In modified k-ε model, besides the value of coefficient, the buoyancy term based on SGDH is modified into GGDH. The strain tensor is modified into rotating tensor to suppress the overestimated local turbulent kinetic energy generated in flow stagnation zone. Comparison between analysis results and experimental data shows that improvement effect of modified model on prediction of light gas stratification erosion rate is significant.